2000
DOI: 10.1007/bf03019475
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ropivacaine 0.1%-fentanyl and bupivacaine 0.125% — fentanyl infusions for epidural labour analgesia

Abstract: Purpose: To compare analgesic efficacies of ropivacaine-fentanyl and bupivacaine-fentanyl infusions for labour epidural analgesia. Methods:In this double-blind, randomized study 100, term, nulliparous women were enrolled. Lumbar epidural analgesia (LEA) was started at cervical dilatation < 5 cm using either bupivacaine 0.25% followed by bupivacaine 0.125% + 2 µg·ml -1 fentanyl infusion (n=50) or ropivacaine 0.2% followed by ropivacaine 0 .1% + 2 µg·ml -1 fentanyl infusion (n=50). Every hour maternal vital sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 13 publications
5
13
1
Order By: Relevance
“…In Group I, the time of onset of analgesia was significantly faster, that is, 9.40±2.37 minutes, as compared to Group II (13.20 ± 2.53 minutes). These results are consistent with studies of Eddleston et al [2] and Finegold et al [3]. Duration of analgesia observed in Group II was longer, that is, 84.38 ± 49.62 minutes, when compared with Group I (76.90 ± 23 minutes).…”
Section: Discussionsupporting
confidence: 92%
“…In Group I, the time of onset of analgesia was significantly faster, that is, 9.40±2.37 minutes, as compared to Group II (13.20 ± 2.53 minutes). These results are consistent with studies of Eddleston et al [2] and Finegold et al [3]. Duration of analgesia observed in Group II was longer, that is, 84.38 ± 49.62 minutes, when compared with Group I (76.90 ± 23 minutes).…”
Section: Discussionsupporting
confidence: 92%
“…A study from our institution found no differences in maternal temperature when infusion of 0.125% bupivacaine and 0.1% ropivacaine were compared, both solutions containing fentanyl. 20 This study found little or no difference in VAS pain scores, local anesthetic usage, duration of labor or mode of delivery. In addition, our sub-analysis failed to show any significant difference between the two solutions.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the extensive use and relative safety of bupivacaine, newer drugs such as ropivacaine and levobupivacaine have been developed to decrease cardiac and neurotoxicity [1,2]. Another advantage of these drugs is the decreased motor block when used in dilute solutions for labor analgesia [3]. There is evidence to suggest that decreased motor block seen with ropivacaine may be a result of decreased potency as compared with bupivacaine [3].…”
Section: Introductionmentioning
confidence: 98%